New lipophilic isoniazid derivatives and their 1,3,4-oxadiazole analogues: Synthesis, antimycobacterial activity and investigation of their mechanism of action - Vosátka, Rudolf; Krátký, Martin; Švarcová, Markéta; Janoušek, Jiří; Stolaříková, Jiřina; Madacki, Jan; Huszár, Stanislav; Mikušová, Katarína; Korduláková, Jana; Trejtnar, František; Vinšová, Jarmila (European journal of medicinal chemistry, 2018)
The development of novel drugs is essential for the treatment of tuberculosis and other mycobacterial infections in future. A series of N-alkyl-2-isonicotinoylhydrazine-1-carboxamides was synthesized from isoniazid (INH) and then cyclized to N-alkyl-5-(pyridin-4-yl)-1,3,4-oxadiazole-2-amines. All derivatives were characterised spectroscopically. The compounds were screened for their in vitro antimycobacterial activity against susceptible and multidrug-resistant Mycobacterium tuberculosis (Mtb.) and nontuberculous mycobacteria (NTM; M. avium, M. kansasii). The most active carboxamides were substituted by a short n-alkyl, their activity was comparable to INH with minimum inhibitory concentrations (MICs) against Mtb. of 0.5-2 μM. Moreover, they are non-toxic for HepG2, and some of them are highly active against INH-resistant NTM (MICs ≥4 μM). Their cyclization to 1,3,4-oxadiazoles did not increase the activity. The experimentally proved mechanism of action of 2-isonicotinoylhydrazine-1-carboxamides consists of the inhibition of enoyl-ACP reductase (InhA) in a way similar to INH, which is blocking the biosynthesis of mycolic acids. N-Dodecyl-5-(pyridin-4-yl)-1,3,4-oxadiazol-2-amine as the most efficacious oxadiazole inhibits growth of both susceptible and drug-resistant Mtb. strains with uniform MIC values of 4-8 μM with no cross-resistance to antitubercular drugs including INH. The mechanism of action is not elucidated but it is different from INH. Obtained results qualify these promising derivatives for further investigation.
Keywords: Oxadiazoles; 2-isonicotinoylhydrazine-1-carboxamide; buňky Hep G2; Antitubercular Agents; Drug Resistance, Bacterial; Microbial Sensitivity Tests; tuberkulóza; Tuberculosis; antituberkulotika; Antimycobacterial activity; 1,3,4-oxadiazole; oxadiazoly; lidé; isoniazid; Humans; bakteriální léková rezistence; mikrobiální testy citlivosti; Hep G2 Cells; Isoniazid; Mycobacterium tuberculosis